The Concept of Love for The Main Character in The Novel “Ancika: Dia Yang Bersamaku Tahun 1995” Pidi Baiq's Works Study of Psychological Literature - Parapat, Putri Erwina Sepiani; Nasution, Ikhwanuddin; Lubis, Haris Sutan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to describe the love relationship of the main character in the novel Ancika Dia Yang Bersamaku Tahun 1995 by Pidi Baiq. This love relationship originates from the main character, Ancika, and Dilan. Starting from their love relationship, the problem arose of finding answers to questions regarding the components of love contained in this relationship. From the interpretation of the components of love, a concept is produced called type of love. The aim of this research is to describe the components of intimacy, components of desire, components of decision and commitment, and the concept of types of love in the novel Ancika Dia Yang Bersamaku Tahun 1995 by Pidi Baiq. The method used in this research is a qualitative method. The approach used is Literary Psychology with a study of Robert J. Sternberg's love triangle theory. Data was collected using note-taking techniques, while data analysis techniques used descriptive techniques. The research results show that the relationship between the characters Ancika and Dilan in the novel Ancika Dia Yang Bersamaku Tahun 1995 has components of intimacy, desire, decision and commitment. From these three components, a concept of a type of love is produced, namely true love. Thus it can be concluded that the relationship between the characters Ancika and Dilan is a relationship of true love.